1975
DOI: 10.1002/aja.1001430205
|View full text |Cite
|
Sign up to set email alerts
|

Morphological effects of a large single dose of cycloheximide on the intestinal epithelium of the rat

Abstract: Adult male rats received 15 mg/kg cycloheximide and the subsequent morphological effects at three and six hours after injection were evaluated using histometry, light and electron microscopy, histological demonstration of terminal web and acid phosphatase, and radioautography with tritiated thymidine. Rapid atrophy of the villi took place, progressing from the villus tip by premature exfoliation of epithelial cells. The crypts also diminished by random exfoliation of many crypt cells and by partial or complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Hence with time after CH, or decreased whereas for most agents it normally increased. In rats, Altmann (1975) has reported somewhat similar effects, namely nectrotic cells on the villus (particularly the villus tip) within a few hours of treatment and extrusion of dead or dying cells (condensed cytoplasm and chromatin) into the lumen of the crypt. These cell migration studies will all be presented in greater detail elsewhere.…”
mentioning
confidence: 74%
“…Hence with time after CH, or decreased whereas for most agents it normally increased. In rats, Altmann (1975) has reported somewhat similar effects, namely nectrotic cells on the villus (particularly the villus tip) within a few hours of treatment and extrusion of dead or dying cells (condensed cytoplasm and chromatin) into the lumen of the crypt. These cell migration studies will all be presented in greater detail elsewhere.…”
mentioning
confidence: 74%
“…In keeping with the notion of "ailing" cells prior to extrusion (Leblond, 1981) and the decline of enzymatic activity (Nordstrom et al, 19681, a general hypothesis has been forwarded that the synthesis and turnover of proteins responsible for cell-to-cell adhesion are altered in enterocytes destined to be lost (Altmann, 1975;Leblond, 1981). Alternatively, a mechanical signal mediated by the cytoskeleton or structural proteins in the junctional complex has been proposed to initiate the extrusion process (Hudspeth, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…One signal posited for the extrusion of senescent cells is the decreased synthesis or degradation of cell adhesion proteins (Altmann, 1975) in concert with a generalized decrease in enzyme synthesis and nuclear atrophy (Leblond, 1981). These changes occur in "predesquamating" cells concentrated in an extrusion zone defined anatomically by intestinal region (Nordstrom et al, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…These included vesiculation of the Golgi apparatus and the rough endoplasmic reticulum to the point that near extrusion, these organelles appeared to be of minimal use so that protein synthesis had to be also minimal. Cycloheximide, an inhibitor of protein synthesis at the translational level, has indeed brought about such vesiculation prematurely as well as a premature extrusion (Falconer, 1982) so that within hours all villus epithelial cells extruded apparently by the normal extrusion mechanism which however was now accelerated (Altmann, 1975). Falconer's study included compacted nucleolus is shown, usually seen in the villus tip columnar cells.…”
Section: Roles Of Protein and Rna Synthesismentioning
confidence: 99%